Current Status of Sodium Bicarbonate in Coronary Angiography: An Updated Comprehensive Meta-Analysis and Systematic Review - Sadegh Ali-Hassan-Sayegh; Seyed Jalil Mirhosseini; Elham Rahimizadeh; Zahra Ghodratipour; Zahra Sarrafan-Chaharsoughi; Ali Mohammad Dehghan; Mohammad Reza Lotfaliani; Mohammad Rezaeisadrabadi; Elham Kayvanpour; Farbod Sedaghat-Hamedani; Mohamed Zeriouh; Alexander Weymann; et al. (Cardiology Research and Practice)
This systematic review with meta-analysis sought to determine comparison of efficacy and safety of hydration with sodium bicarbonate versus sodium chloride on contrast induced nephropathy and clinical outcomes. We searched major electronic databases for studies in randomized controlled trials. A value of P<0.1 for Q test or I2>50% indicated significant heterogeneity between the studies. Literature search of all databases retrieved 650 studies. 29 studies enrolled in meta-analysis. Pooled analysis indicated about the incidence of CIN (OR of 0.718; 95% CI: 0.60 to 0.85; P=0.000), requirement of hemodialysis (OR of 1.00; 95% CI: 0.49 to 2.01; P=0.9), mean changes of serum creatinine (WMD of 2.321; 95% CI: 1.995 to 2.648; P=0.000), length of hospital stays (WMD of −0.774; 95% CI: −1.65 to 0.10; P=0.08), major adverse cardiovascular events (OR = 1.075, 95% CI: 0.59 to 1.95; P=0.8), and mortality (OR of 0.73; 95% CI: 0.42 to 1.26; P=0.2). Overall, hydration with sodium bicarbonate could significantly reduce CIN and the length of hospital stay compared to sodium chloride. In addition NAC added as a supplement to sodium bicarbonate could increase prophylactic effects against nephropathy.